FACTOR INFLUENCING QUALITY OF LIFE AMONG CAREGIVERS CARING FOR PATIENTS WITH SCHIZOPHRENIA IN COMMUNITY - แสงรักษา, โชคพิพัฑฒน์; แนบเกษร, ชนัดดา; วัฒนสินธุ์, ดวงใจ (Primary Health Care Journal (Northeastern Edition), 2025)
Schizophrenia is a common mental disorder characterized by disturbances in thought, emotion, perception, and behavior. Caregivers of individuals with schizophrenia play a critical role, as they face physical, emotional, and financial burdens that may adversely affect their quality of life. This predictive correlational study aimed to examine the quality of life and its influencing factors among caregivers of people with schizophrenia. A simple random sample of 110 community caregivers in Ubon Ratchathani Province completed self‑report questionnaires in October 2023. Data were analyzed using descriptive statistics and stepwise multiple regression. Results indicated that 69.1% of caregivers had a moderate overall quality of life (Mean = 85.71, SD = 16.38). Two factors emerged as statistically significant predictors: caregiving burden (β = -0.302, p < .001) and social support (β = 0.276, p < .05). Together, these variables explained 19.3% of the variance in quality of life (R² = 0.193, F(2, 107) = 12.79, p < .05). In conclusion, most caregivers of individuals with schizophrenia reported moderate quality of life. To enhance caregivers’ well‑being, interventions should focus on reducing caregiving burden and bolstering social support.